Halicephalobus gingivalis (H.deletrix) in the brain of a horse - Vasconcelos, Rosemeri de Oliveira [UNESP]; Lemos, Karen Regina; Moraes, Julieta Rodini Engracia de [UNESP]; Borges, Vívian Palmeira (Universidade Federal de Santa Maria (UFSM), 2007)
Um eqüino macho, com 10 anos, Mangalarga, apresentou uma infecção por um nematódeo rabditiforme no cérebro. Os sinais clínicos limitaram-se ao fato de o animal andar em círculos e apresentar paralisia do lado direito. O exame histológico do cérebro revelou acentuada gliose e discreto edema intersticial. O infiltrado inflamatório mononuclear perivascular era composto por poucas camadas de linfócitos, plasmócitos, macrófagos e raros eosinófilos, associados aos nematódeos rabditiformes. Áreas de malácia e trajetos com esferóides axonais são vistos ao redor de vasos e do agente etiológico, sendo mais evidentes na substância branca. Nas meninges, o infiltrado inflamatório foi moderado e associado a parasitas perivasculares. A identificação do nematódeo foi baseada no exame histológico do cérebro do cavalo.

A 10-year-old Mangalarga gelding with rhabditiform nematode infection in the brain is described. Clinical signs were limited to circling and right side paralysis. Histological examination of the brain revealed marked gliosis and discreet edema. The perivascular mononuclear inflammatory infiltrate was composed of few layers of lymphocytes, plasmocytes and macrophages and rare eosinophils. The presence of rhabditiform nematodes was associated with the infiltrate. Areas of malacia associated with the parasites and parasite tracks with axonal spheroids were also seen close to the vessels and to the etiological agent and were more evident in the white matter. In the meninges there was moderate inflammatory infiltrate associated with perivascular parasites. The identification of the nematode was based on the histological examination of the cerebral fragments.
Halicephalobus gingivalis (H.deletrix) no cérebro de um eqüino
Keywords: Nematode; Equine; Central nervous system; Micronema deletrix; Nematódeo; Equino; Sistema nervoso central; Micronema deletrix